2009
DOI: 10.1103/physrevb.80.035113
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the mass enhancement inCaCu3Ru4O12

Abstract: We have investigated heavy-fermion behavior of the transition-metal oxides ACu 3 Ru 4 O 12 ͑A = Na, Ca, La, and their mixtures͒. It has been known that CaCu 3 Ru 4 O 12 exhibits Kondo-like behavior attributable to Cu 2+ 3d electrons, similar to that of some Ce-based heavy-fermion systems. However, we find striking suppression of the mass enhancement in CaCu 3 Ru 4 O 12 , in which the Kondo-type effect is most pronounced. Such decrease in the density of states is reminiscent of the coherent-gap formation in Kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…This, in turn, makes the hybridization between the Cu sublattice and B sublattice weaker and weaker since those ions communicate via the intervening oxygen. This highlights a key difference between CCIrO and CaCu 3 Ru 4 O 12 , where for the later it was found that the suspected Kondo-like physics was unlikely due to a strong mixing of Cu with O [40,41]. Similar to that of high T c cuprates, for CCCoO the O p states are positioned above Cu d x 2 −y 2 , placing Cu in to a negative charge transfer regime which promotes a high-T c cuprate like d 9 L state akin to the Zhang-Rice singlet state [24][25][26]42].…”
Section: Dft Resultsmentioning
confidence: 92%
“…This, in turn, makes the hybridization between the Cu sublattice and B sublattice weaker and weaker since those ions communicate via the intervening oxygen. This highlights a key difference between CCIrO and CaCu 3 Ru 4 O 12 , where for the later it was found that the suspected Kondo-like physics was unlikely due to a strong mixing of Cu with O [40,41]. Similar to that of high T c cuprates, for CCCoO the O p states are positioned above Cu d x 2 −y 2 , placing Cu in to a negative charge transfer regime which promotes a high-T c cuprate like d 9 L state akin to the Zhang-Rice singlet state [24][25][26]42].…”
Section: Dft Resultsmentioning
confidence: 92%
“…Studies on the substitution of Ca by La and Na reveal that only for CaCu 3 Ru 4 O 12 the broad maximum in the magnetic susceptibility around T * is pronounced, while the γ coefficients are large in all compounds, with CaCu 3 Ru 4 O 12 having the smallest γ. 14,15 Up to date, there is no consensus on the details of the mechanism for the enhanced Sommerfeld coefficient, the unusual magnetic behavior, and the validity of the Kondo scenario.…”
Section: Introductionmentioning
confidence: 99%
“…The results give us interesting aspects behind the mechanism of excitation energy transfer in photosynthetic system [16,17], and may play a role in the formation of solitons and quantum thermal sound modes in molecular chains [5,6,18]. Closely related results were also found in the spin-boson model applied to photosynthetic system [19], double quantum dot charge qubit system [20], and by taking the coherent superposition of excitations and vibrational states into consideration [21].…”
Section: Introductionmentioning
confidence: 55%
“…In this case, α hx is proportional to the square of the ratio between the time scale for sound wave to traverse adjacent sites, a/v, and the time scale for the vibrational mode to move from one site to another via intersite coupling, 1/J 12 . Using the value J 12 = 7.8 cm −1 , a = 4.5Å, and v = 4000 m/s at physiological temperature 310 K [6,18], we obtain a longer relaxation time scale of about 1/α = 36.6 times that of the dephasing time scale of the individual site in a phonon bath. Such a prolonged relaxation time scale and the existence of metastable in each fixed exciton number subspace may facilitate the formation of solitons [5,6] or quantum thermal sound modes in this system [18].…”
Section: B Alpha-helix Protein Molecular Chainmentioning
confidence: 99%